Pengaruh Latihan Pitch-Matching Terhadap Akurasi Menyanyi Siswa Sekolah Dasar - Kurniawan, Muhamad Arif; Julia, Julia; Gusrayani, Diah (Jurnal Pena Ilmiah, 2019)
One of the problems that occurs today is the low ability of student’s singing accuracy. The purpose of this study was to determine the differences in the increase in the student’s singing accuracy in the experimental class who did pitch-matching exercises with the control class that did conventional learning without pitch-matching exercises. The design of this study was quasi-experimental with nonequivalent control group design. The sample in this study were 30 students in the experimental class and 31 students in the control class. Based on the results of the study, the average value of students in the experimental class increased from 40 to 68.8, while in the control class the average value of students increased from 33.5 to 40. However, based on the results of statistical tests that there were differences in improvement which indicated an increase in class the experiment was higher than the control class.